Contrary to the actual condition and the answer in the Koran - محمد محمود عماد; جاسم عبود محمد (Al-Adab Journal, 2018)
Offset between the acts is displayed in the Arabic language in general and more specifically the Holy Qur’an, which comes for the purposes of semantic and stylistic different, and is linked to this phenomenon violates the actual condition and the answer in time. Grammarians have decided that the best method in the condition is that really comes requirement and answer Madian, then Mdharaan, and what was otherwise tried to be interpreted. This research proved that the rules established by grammarians do not stand too much in front of the reported examples of this phenomenon in the Koran, and that the cause offset time between the actual condition and the answer - especially in the event that the reaction condition past and did answer Mdharaa - but due to reasons semantic and contextual responsible for all resource Quranic text came to talk with him or Inh.